Lysosomal Storage Disease in Iran (Report of Molecular Study) - HOUSHMAND, Massoud; TONEKABONI, Seyed Hassan; KARIMZADEH, Parvaneh; ARYANi, Omid; ASHRAFI, Mahmoudreza; SALEHPOUR, Shadab; BADV, Shervin; SHAKIBA, Marjan; ALAEE, Mohammad Reza; FARSHIDI, Shahla (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Houshmand M, Tonekaboni SH, Karimzadeh P, Aryani O, AshrafiMR, Salehpour Sh, Badv Sh, Shakiba M, Alaee MR, Farshid Sh. Lysosomal Storage Disease inIran. (Report of Molecular Study). Iran J Child Neurol Autumn 2012; 6:4 (suppl. 1): 22. Pls see PDF.